The Problem of Local Authority Insolvency - Mateusz Langer (Prawo Budżetowe Państwa i Samorządu, 2014)
In this article, there has been undertaken the specific problem of local authority insolvency, and a diverse anti-bankruptcy methods which enforce against the insolvency. The first section describes the particular role of local authority insolvency, as well as the essence of this phenomenon in modern countries. Another part of the work revives different types of anti-bankruptcy methods. However, the last section summarizes the analyzed topics.